BUILDING BRAND EQUITY THROUGH SOCIAL MEDIA INFLUENCER: A STUDY ON SOCIAL MEDIA INFLUENCER IN SAUDI ARABIA - Esraa Almakbuli, Saima Khan, Manzar Ahmed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of this study is to transferring the concept of customer-based brand equity (CBBE) to understand the significance impact of celebrity endorsement on it, and shows the relationship between the influencer and customer behavior. This study also determines the important social media influencers are in building brand equity. Brand equity involves all business strategies also it related to brand loyalty, brand love and purchases intense. Moreover, successful brand equity gives a strong image and competitive advantages. This study proposed that brand equity affect the social media influence. A survey-based quantitative approach is used with fans and people who follow the influencer to test the proposed hypothesis. The data were collected through distributing the online and offline survey and were analyzed using two different tests namely one-way Anova and correlation test. The findings indicate that there is a relationship between brand equity and influencer the result shows the impact is there however the strong is not that much.